Qur'an Literacy Crisis in Alpha Generation in Rural Indonesia: A Case Study of Social, Digital, and Family Factors - Siti Nur Khusnul Khotimah; Anita Dewi Laksono (Yayasan Pendidikan Haiba Nasywa, 2026)
This study aims to comprehensively analyze the low interest of the Alpha Generation in learning the Qur'an through a case study in Mandiraja Village, Pemalang Regency, Indonesia. Using a qualitative approach with a case study design, data was collected through unstructured interviews, participatory observation, and document analysis, then analyzed using Miles and Huberman's interactive model with triangulation of source and method triangulation validation to ensure strict data validity. The results of the study reveal three fundamental findings regarding contemporary socio-religious challenges in rural Java. First, the decline in interest is caused by the dominance of gadgets that offer instant gratification, weak parental supervision due to economic busyness, and conventional TPQ methods. Second, gadgets distort the pattern of time reading through the mechanism of time substitution, attention fragmentation, and conditional negotiation where gadgets become rewards before reciting which creates chronic time conflicts. Third, countermeasures involve the strategic role of parents and religious leaders through digital disciplinary supervision, direct examples, and collaboration of innovative programs despite the constraints of consistency in the field. Overall, this crisis is not purely an individual problem but a failure of social ecosystems to adapt to digital disruption, where gadgets are becoming serious competitors to the Qur'an in competing for the attention of the rural younger generation. Holistic interventions involving technology, parenting, and curriculum are a strategic urgency to save religious traditions in Mandiraja, Pemalang Regency, Indonesia from the threat of moral degradation and the extinction of sacred literacy. This research contributes to filling the literature gap regarding the dynamics of socio-religious facts in the context of digital transition in the Alpha generation in rural Central Java and provides an empirical basis for local Islamic education policies that are more adaptive to changing times for the sustainability of Islamic identity in future generations and prevent social anomie in rural communities in transition.